The Question about the Hypertextual Relations in the Book of Genesis Still Open - Pikor, Wojciech (The Biblical Annals, 2024)
The article is a critical review of the commentary by Bartosz Adamczewski – Genesis. A Hypertextual Commentary. After presenting the theses put forward by Adamczewski in his commentary on Genesis, the criteria of sequential hypertextuality implemented by Adamczewski and his method of delimiting literary units that remain in hypertextual relations are critically reviewed. The methodological weakness of the hypertextual commentary on Genesis cannot be covered up by the creativity of the commentator.